Exact Computation of Pearson Statistics Distribution and Some Experimental Results - Filina, Marina V.; Zubkov, Andrew M. (Österreichische Zeitschrift für Statistik, 2016)
A Markov chain based algorithms for exact and approximate computation of Pearson statistics distribution for multinomial scheme are described. Results of computational experiments reveal some new properties of the difference between this distribution and corresponding chi-square distribution.